2009
DOI: 10.1007/s00535-009-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic role of the tyrosine-phosphorylated CagA EPIYA sequence of Helicobacter pylori in histological gastritis in Japanese patients

Abstract: CagA-P is an antigen-peptide against the host, and serum titer of anti-CagA-P antibody may be a new marker for gastritis in the corpus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…As shown in table 3, we could not demonstrate any differences in these classical serological markers between the AG group and the DGC group. We previously confirmed that the titers of anti-CagA-P antibodies in the sera of H. pylori -positive patients were statistically higher than those of H. pylori -negative patients [12]. Interestingly, we found that the serum titer of anti-CagA-P antibody in the patients of the DGC group was statistically higher than the titer of those of the AG group, especially in females (p< 0.05, fig.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…As shown in table 3, we could not demonstrate any differences in these classical serological markers between the AG group and the DGC group. We previously confirmed that the titers of anti-CagA-P antibodies in the sera of H. pylori -positive patients were statistically higher than those of H. pylori -negative patients [12]. Interestingly, we found that the serum titer of anti-CagA-P antibody in the patients of the DGC group was statistically higher than the titer of those of the AG group, especially in females (p< 0.05, fig.…”
Section: Resultssupporting
confidence: 71%
“…The slides were incubated in 0.1% trypsin (Becton, Dickinson and Company) for 30 min at 37°C for antigen retrieval [16] followed by an immunoreaction with the primary antibody in PBS overnight at 4°C. We used originally raised anti-CagA-P antibody (OF-515) as the primary antibody with a 1:200 dilution [12]. After immunohistochemical staining had been performed using the LSAB2 System-HRP kit (Dako, Kyoto, Japan), the sections were finally lightly counterstained with Mayer’s hematoxylinsolution (Merck KGaA, Germany), intensified,dehydrated, and mounted for quantitative analysis.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations